Respect for Autonomous Risky Decisions and People with IDD: Prioritizing Healthcare Provider Trustworthiness - Bianchi, Andria (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2025)
Autonomy is a primary guiding healthcare ethics principle in Western liberal societies. Generally speaking, the principle means that we ought to respect individuals’ decisions in relation to themselves, even when such decisions are risky from some perspectives. The principle of autonomy may be of particular importance when thinking about marginalized populations whose ability to make autonomous decisions, and to have such decisions respected (by enabling the autonomous decision to occur through positive or negative means), was largely, historically non-existent. One of these populations is people with intellectual and developmental disabilities (IDD). When it comes to a person with IDD making an autonomous risky decision, a clinician may respect their decision because of the typical weight and priority given to the principle of autonomy. However, this paper argues that a person with IDD’s autonomous risky decision related to care provision should only be respected insofar as the clinician has demonstrated trustworthiness in an effort to obtain trust. In other words, I argue that unless a clinician has demonstrated that they are trustworthy, then a risky autonomous decision related to care provision should not be immediately respected when working with a person with IDD. The reason that a risky autonomous decision should not be respected unless there is demonstrated trustworthiness is because of how trustworthiness may influence decision-making insofar as trust is gained. If a person with IDD makes a risky decision without finding their provider to be trustworthy, then their decision may be unnecessarily motivated by lack of trust. There are good reasons that a person with IDD may not find their clinicians to be trustworthy, hence the rationale for ensuring the intentional demonstration of trustworthiness before respect for autonomous risky decision-making.